Assessing the use of telehealth for the surgical management of recurrent otitis media. (February 2022) - Schafer, Austin; Mousset, Marike; Kelly, Natalie; Althubaiti, Abdulrahman; Bourgeois, Tran; Elmaraghy, Charles A.
Abstract: Objective: To compare the incidence of middle ear effusion (MEE) at the time of bilateral tympanostomy tube insertion (BTI) for recurrent acute otitis media (rAOM) patients initially seen in-office or via telehealth. Methods: After obtaining IRB approval from Nationwide Children's Hospital, a total of 524 patients evaluated for rAOM were retrospectively reviewed after being divided into two cohorts: those seen via a telehealth visit from April to June of 2020 (n = 140), and those seen via an in-person visit from April to June of 2019 (n = 384). Recommendation for BTI was captured for each patient following their visit. Clinical characteristics documented at the time of the visit, such as history of intramuscular (IM) antibiotic use and hearing or speech concerns were also captured to determine whether both telehealth and in-person cohorts were similar in clinical presentation. For BTI patients, the presence or absence of MEE in either ear at the time of BTI was recorded. Patients with cleft palate or prior BTI were excluded. Results: 51.43% (72/140) of patients in the telehealth cohort were recommended for BTI. Of those recommended, 87.50% (63/72) underwent BTI. Of these, 31.75% (20/63) had a MEE at the time of BTI. In the in-office cohort, 69.01% (265/384) of patients were recommended for BTI. Of those recommended, 92.83% (246/265) underwent BTI. Of these, 69.92% (172/246) had a MEE at the time of BTI. Conclusion: There were significantly less middle ear effusions in the telehealth cohort compared to the in-office cohort (p < 0.0001). It is well understood that telehealth is limited in its physical exam capabilities. It is possible that the use of telehealth for the surgical management of rAOM may lead to more procedures on patients without MEE.